An exploratory study of metaphor types and tasks - Siman, Josie Helen (2022)
How do people interpret metaphors? The goal of this paper is to acknowledge metaphors’ complexity beyond the scope of any specific theory of metaphors. Instead of ignoring contradictory findings, we propose to highlight and analyze regularities and irregularities in our findings, using insights from complex systems science to guide our discussions. In this exploratory study, participants were asked to substitute a metaphor vehicle for a word with a similar meaning and to explain the analogical motivation of the metaphor. There were three types of metaphors: primary, complex, and predicative. This is the first study to compare these three types of metaphors across two different tasks. Results show how metaphors cluster according to its type, but not uniformly. In this quantitative and qualitative analysis, we also show that multiple sources of experiences are available during metaphor interpretation. In conclusion, we highlight that no current theory can accommodate and predict all types of metaphoric behavior different people display in different contexts, but we understand some of the major biases and factors that are involved in metaphor interpretation.